Children’s voices through teachers’ stories - Elisabetta Musi; Margareth Eilifsen (The Indo-Pacific Journal of Phenomenology)
We understand our lives through narratives, and the form of these narratives is appropriate for understanding the actions of others, writes MacIntyre (1981). Meanwhile, narratives and our understanding of them also inform our understanding of our own actions. In this article, student kindergarten teachers share anecdotes from their teaching practice assignments. These preservice teachers (PSTs) relay stories that are serious and important from a child’s perspective, and which they themselves experienced as serious and important while spending time with children and listening to children’s voices. Our aim here is to give even very young children a voice in their own everyday lives and to discuss how PSTs might listen more closely to what children are saying. Our narrative analysis of stories (Van Manen, 1997, 2014; Clandinin, 2013) offered by Norwegian and Italian PSTs presents a range of perspectives on life management and a desire for conversation in children aged 2–8 years. The stories are told through the student kindergarten teachers’ voices, and they were shared with and reflected upon with the children’s in-service class teachers. The article sheds retrospective light on children’s telling of, and thinking about, stories.